Assessment of risk, severity, mortality, glycemic control and antidiabetic agents in patients with diabetes and COVID-19: A narrative review. (July 2020) - Singh, Awadhesh Kumar; Khunti, Kamlesh
Highlights: Diabetes is associated with a significantly increased severity and mortality with COVID-19, even in the absence of other comorbidities. Uncontrolled hyperglycemia is a risk factor for increased severity and mortality in patients with COVID-19. Although data is scarce at the moment, no anti-diabetic agents so far appears to have any favorable or unfavorable effects in patients with COVID-19. Abstract: Aims: Rising prevalence of non-communicable diseases world-wide has made diabetes an important comorbidity in patients with coronavirus disease-19 (COVID-19). We sought to review the risk, severity and mortality in COVID-19 and its relation to the glycemic control, and role of anti-diabetic agents in patients with diabetes. Methods: A Boolean search was made in PubMed, MedRxiv and Google Scholar database until May 10, 2020 and full articles with supplementary appendix were retrieved using the specific key words related to the topic. Results: There is a high prevalence of diabetes in patients with COVID-19. Patients with diabetes had a significantly more severe variety of COVID-19 and increased mortality, compared to the groups without diabetes. Moreover, poor glycemic control is associated with a significantly higher severe COVID-19 and increased mortality, compared to the well-controlled glycemic groups. No data currently available for or against any anti-diabetic agents in COVID-19. Conclusions: Diabetes, in particular poorly-controlled group is associated with a significantly higher risk of severe COVID-19 and mortality. This calls for an optimal glycemic control and an increased emphasis on future preventative therapies including the vaccination programs for these groups in addition to the traditional risk prevention such as social distancing and self-isolation.